Effect of oral anticoagulants on hemostatic and thromboembolic complications in hip fracture: A systematic review and meta‐analysis. (23rd July 2020) - Xu, Yan; You, Daniel; Krzyzaniak, Halli; Ponich, Brett; Ronksley, Paul; Skeith, Leslie; Salo, Paul; Korley, Robert; Schneider, Prism; Carrier, Marc
Abstract: Background: Hip fracture patients on oral anticoagulants (OACs) experience increased time‐to‐surgery and higher mortality compared to non‐anticoagulated patients. However, it is unclear whether pre‐injury OAC status and its associated operative delay are associated with worsening of peri‐operative hemostasis or an increased risk of postoperative thromboembolism. Methods: We performed a systematic review to identify studies that directly compared hemostatic and thromboembolic outcomes among hip fracture patients on an OAC prior to admission with those not on anticoagulants. Random effects meta‐analyses were used to pool all outcomes of interest (estimated blood loss, transfusion requirements, and postoperative thromboembolism). Results: Twenty‐one studies involving 21 417 patients were included. Estimated blood loss was higher among patients presenting with OACs compared to those not anticoagulated (mean difference 31.0 mL, 95% confidence interval [CI] 6.2‐55.7). Anticoagulated patients also had a 1.3‐fold higher risk of receiving red blood cell transfusions (odds ratio [OR] 1.34, 95% CI 1.20‐1.51); however, rates of postoperative thromboembolism were similar regardless of anticoagulation status (OR 0.96, 95% CI 0.40‐2.79 for venous thromboembolism; OR 0.58, 95% CI 0.25‐1.36 for arterial thromboembolism). No subgroup effect was found based on anticoagulant type or degree of surgical delay. Conclusion: Hip fracture patients on OACs experience increased surgical blood loss and higher risk of red blood cell transfusions. However, the degree of surgical delay did not mitigate this risk, and there was no difference in postoperative thromboembolism. The impact of appropriate, timely OAC reversal on blood conservation and expedited surgery in anticoagulated hip fracture patients warrants urgent evaluation.